PERENCANAAN PROSES TUNGKU PENGERING KOTORAN HEWAN TERNAK - Perwira, Cholyan; Burhanuddin, Yanuar; Yahya TP, Ahmad (FT UNILA, 2014)
Most welding shops in the area Pringsewu District in carrying out the work are still using a system that is not working or is not systematically planned, which is why most welding shops suffered many losses, such as product processing time is longer, the cost of production incurred greater and workmanship unsatisfactory. Of the shortcomings and weaknesses of the system working in most welding shops in the Pringsewu District, it is necessary to study the process planning , which is applied in the manufacture of livestock manure dryer furnace in the manufacturing process in a small welding shop. This study aims to make a good process planning that can be applied to the world of entrepreneurship, especially welding shop. The research was conducted at the welding shop at Pringsewu district in January-March 2013. Making the process planning begins with the creation of images 2dimensional furnace consists of 4 major components, namely cones, combustion chamber, body coatings, and disposal space. Procedures sheets gained as much as 11 pieces that serve to minimize material and wasted time . Calculation time of making the furnace obtained through primary and secondary data collection that results in two sketches workplace assembling component parts, 41 pieces of the map left and right hand and 8 pieces of the process flow map. The resulting time using MOST (Mynard Operation Sguence Technique) is equal to 57.8757 hours divided by 8 hours of working time in 1 day = 7.2344625 days or ± 8 days. The total estimated cost of production based on direct costs, indirect costs, and overhead costs for Rp.8.345.300Keywords : Process planning, Furnace, Procedures sheet, MOST